Habitus and labeling of at-risk school dropout children at the high school level in Lamongan Regency - Lana Faiqoh Zahiroh; Maybe Zenengene (Department of Sociology, Faculty of Social and Political Sciences, Universitas Airlangga, 2023)
Children who are at risk of dropping out of school are a social problem in the field of education. This study aimed to determine the habitus and labeling of at-risk school dropout children at senior high schools in the Lamongan Regency. The theoretical framework used was the Habitus theory proposed by Pierre Bourdieu and the Labeling theory by George Herbert Mead. This study employed qualitative methods. The informants in this study were high school students or equivalent. This study found that habitus among at-risk school dropout children leads to deviant behavior and labeling. This can encourage children to drop out of school. In addition, fields and capital also do not support children in studying. Children’s problems are also seen in the deviations committed both in the social and educational environment. That is what makes children have a label or nickname in society and their peer environment. This study can be used to inform government policies in the field of education, particularly in dealing with children prone to dropping out of school. In this case, the involvement of schools, teachers, parents, and the community is also essential.